Effect of Long Storage on Room Temperature on Changes of Physicalchemical Characteristics of Frozen Edamame, Glycine max (L) - Anisa Aprilia (Gontor AGROTECH Science Journal, 2020)
Edamame is an agricultural product famous as vegetable soybeans. One of the edamame processed product is frozen edamame. Frozen edamame is a unique product frozen of souvenirs from jember. This product is vulnerable to quality degradation due to the environment and consumer treatment. Consumers buy and carry product for souvenirs in a long journey and consumers are less precise in handling storage again when out of frozen storage. This study aims to improve the impact of space temperature storage with different time to physical quality and chemical seeds and the old influence of storage with different time to the original organoleptic characteristics of frozen edamame. The result of tests conducted on the original edamame product during storage at room temperature affect the physical and chemical products as follows: a green color 0.69 while the color leads to red 4.68, color b is 4.77, color C is 4.7, texture value is 0.47 mm/10secon, total dissolved solids by 2.080Brix, pH values 1.33%, total acids by 0.005%, moisture content 4.5% and antioxidant actives by 0.69 µg / mL